2006
DOI: 10.1186/1479-5876-4-48
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and cancer progression: the emerging role of interleukin-1 receptor antagonist as a novel therapeutic agent in cancer treatment

Abstract: The tumor microenvironment consists of tumor, immune, stromal, and inflammatory cells which produce cytokines, growth factors, and adhesion molecules that promote tumor progression and metastasis. Of particular interest in this setting is interleukin-1 (IL-1), a pleiotropic cytokine with numerous roles in both physiological and pathological states. It is known to be up regulated in many tumor types and has been implicated as a factor in tumor progression via the expression of metastatic and angiogenic genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(197 citation statements)
references
References 43 publications
5
189
0
3
Order By: Relevance
“…IL-1 signaling can play an important role in immune or stromal cells as well as within the cancer cells themselves. 27 In the current study, we did not pinpoint the location of either the cytokine or the receptor within the host. Future studies would be required to understand in which cell type IL-1a and IL-1R1 are important and whether IL-1a acts in an autocrine or paracrine fashion.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…IL-1 signaling can play an important role in immune or stromal cells as well as within the cancer cells themselves. 27 In the current study, we did not pinpoint the location of either the cytokine or the receptor within the host. Future studies would be required to understand in which cell type IL-1a and IL-1R1 are important and whether IL-1a acts in an autocrine or paracrine fashion.…”
Section: Discussionmentioning
confidence: 83%
“…24 These and other studies 25,26 have led to the proposal that IL-1R1 blockade might constitute a potential cancer therapeutic. 9,10,27 However, although IL-1b signaling has been reported to drive carcinogenesis, many studies have shown an antitumorigenic role for IL-1a. 7,21,[28][29][30][31] For instance, NIH3T3 fibrosarcoma cells transfected with IL-1a failed to grow in vivo following i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, patients harboring IL-1-positive tumors have markedly worse prognoses (Lewis et al, 2006). Due to its pleiotropic nature, IL-1 promotes tumor growth and metastasis in an autocrine/paracrine manner.…”
Section: Il-1 and Tnfmentioning
confidence: 99%
“…Interleukin-1␤ (IL-1␤) 3 is a pleiotropic pro-inflammatory cytokine involved in cell growth, differentiation, tissue repair, and regulation of immune response (4). IL-1␤ is often detected in human cancer tissues including breast cancer, pancreatic cancer, glioblastoma, and melanoma (5)(6)(7)(8)(9)(10)(11)(12)(13), where the expression levels of the IL-1␤ protein or gene are associated with the invasiveness and metastasis of cancers. Experiments using exogenously administered IL-1 or IL-1 knock-out mice suggest that stromal-derived IL-1 plays an important role in the progression of murine tumors (14 -19), whereas recent reports have shown that tumor-derived IL-1␤ is associated with tumor growth, immunosuppression, and chemoresistance (7,8,13,15).…”
mentioning
confidence: 99%